Instructional Media Development for Teaching Japanese Language - Firmansyah, Dian Bayu; Rahmawati, Riska Sri; Tanzil, Andini Qodriya (LPPM Undiksha, 2018)
This research aims to develop multimedia teaching materials for teaching Japanese language at the senior high school. Using Adobe Flash CS5 software, this interactive media was technology based and provided some features found in the source book, such as vocabularies or sentence patterns introduction, etc. In addition this media also equipped by Japanese words pronounciation practice using Online Japanese Accent Dictionary (OJAD). This research was conducted with pre-experimental method, survey questionnaire and a short interview. Research subjects were teachers and students of senior high schools majoring Japanese language in Indonesia. Survey questionnaire result showed that this media was high rated as an attractive media and user-friendly media based on the contents and features provided on it. Further, it was found that this media was very useful not only for teachers as a teaching materials, but also for learners who are eager to learn Japanese independently.